О времени выхода в свет отдельного издания «Охранной грамоты» Бориса Пастернака [Concerning the Publication Date of Boris Pasternak’s _Safe Conduct_ First Edition] - Salman, Marina (Slavica Revalensia, 2023)
This paper aims to show that Boris Pasternak’s Safe Conduct was published two months before what was previously thought to be the book’s official publication date—not in November 1931, but in the early September. The article also provides some previously unknown information about Valentin Stenich (Valentin Smetanich).